Wpływ kształcenia zawodowego na rozwój fizyczny dziewcząt - Gołębiowska, Maria; Grabowska, Jadwiga; Łuczak, Bogdan; Chlebna-Sokół, Danuta; Stańczyk, Anna (Polskie Towarzystwo Antropologiczne, 1987)
The comparison of the physical development of giris attending two type of secondary school: professional and general education secondary school has shown differences following mainly from the existence of a preliminary selection conditioned by the social and somatic factors.
The influence of professional education on the physical, development of girls